2013
DOI: 10.1007/s11011-013-9460-9
|View full text |Cite
|
Sign up to set email alerts
|

Depo-Provera effects on Wistar rat performance in the Y-maze

Abstract: Medroxyprogesterone acetate is the most commonly used progestin component of hormone therapy. The goal of the present study was to determine whether Medroxyprogesterone affects rat behavior using a Y-maze test. Twenty-four female Wistar rats were randomly selected into three groups; control group, a low dose (13 mg/ml MPA) group and a high dose (33 mg/1 ml MPA) group. Doses of Medroxyprogesterone were delivered by intramuscular injection for a period of 3 weeks. Medroxyprogesterone administration resulted in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Limiting the duration of treatment did not reduce the magnitude of the cognitive effect, as findings from Braden et al [8] were replicated. Other rodent studies have shown that long-term treatment of 17β-estradiol plus MPA led to impaired spatial memory performance, as compared to 17β-estradiol, in Ovx rats [10, 11]. Additionally, in young Ovx mice, MPA treatment reversed the cognitive benefits seen with progesterone alone [52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Limiting the duration of treatment did not reduce the magnitude of the cognitive effect, as findings from Braden et al [8] were replicated. Other rodent studies have shown that long-term treatment of 17β-estradiol plus MPA led to impaired spatial memory performance, as compared to 17β-estradiol, in Ovx rats [10, 11]. Additionally, in young Ovx mice, MPA treatment reversed the cognitive benefits seen with progesterone alone [52].…”
Section: Discussionmentioning
confidence: 99%
“…Further, MPA is the only active ingredient in the contraceptive Depo Provera, and a documented case study revealed amnestic effects associated with its use [7]. In animal models, MPA has been associated with memory impairments across the adult lifespan [811] as well as adverse cellular effects in vitro [1214]. Given the evidence that use of MPA in HT and contraceptives has potentially deleterious effects, it is imperative to determine an alternative progestin that is safer for women’s health, not only to prevent endometrial hyperplasia, but also to protect the brain and its function.…”
Section: Introductionmentioning
confidence: 99%
“…Women that have a uterus must include a progestogen in their HT regimen to protect against endometrial hyperplasia (Smith et al, 1975 ). The most commonly prescribed progestin component of HT, and the sole hormone component of the contraceptive Depo Provera, medroxyprogesterone acetate (MPA), has been associated with memory impairments in rodent models across the adult lifespan (Braden et al, 2010 , 2011 ; Lowry et al, 2010 ; Okojie and Oyekunle, 2014 ) and adverse in vitro cellular effects (Nilsen and Brinton, 2002b ; Nilsen et al, 2006 ). There is evidence in postmenopausal women that combination HT treatment including MPA increases the risk of dementia (Shumaker et al, 2003 ; Coker et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the Women's Health Initiative and ancillary data have indicated a negative impact of combined HT as well; CEE plus MPA significantly increased dementia risk while CEE only yielded a non-significant increased risk, and CEE versus CEE plus MPA yielded different verbal memory effects [62,[78][79][80][81]. MPA impairs memory in rodent models across the adult lifespan, showing effects that are long-lasting and potentially non-reversible [82][83][84][85]. Detrimental cellular effects with MPA administration have also been observed, including exacerbation of glutamateinduced excitotoxicity, attenuation of estrogen-induced neuroprotection in hippocampal neuronal cell culture [86,87] and altered glutamic acid decarboxylase (GAD)65 þ 67 expression in the hippocampus and entorhinal cortex of middle-aged Ovx rats [82].…”
Section: Use Of Progestogensmentioning
confidence: 99%